2021
DOI: 10.1016/j.jbc.2021.101209
|View full text |Cite
|
Sign up to set email alerts
|

DNA-PKcs kinase activity stabilizes the transcription factor Egr1 in activated immune cells

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…DNA-PKcs phosphorylates the serine/threonine kinase AKT at serine 473 resulting in kinase activation. 23,27 AKT is phosphorylated in T cells following stimulation. This is required for downstream signaling which promotes the shift to aerobic glycolysis to support increased proliferation and gene transcription in activated T cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA-PKcs phosphorylates the serine/threonine kinase AKT at serine 473 resulting in kinase activation. 23,27 AKT is phosphorylated in T cells following stimulation. This is required for downstream signaling which promotes the shift to aerobic glycolysis to support increased proliferation and gene transcription in activated T cells.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we determined DNA-PKcs is required for the activity of the transcription factors NFAT, NF κ B and EGR1 and production of cytokines critical to T cell function, including IL2, IL6, IFN γ , and TNFα. 2123 Moreover, we showed that treatment with the DNA-PKcs inhibitor NU7441 extended the survival of transplanted allogenic skin grafts in a murine mouse model by reducing T cell-graft infiltration and inflammatory cytokine production. 22 These studies highlight the immunosuppressive effects of DNA-PKcs inhibitors and suggest the potential repurposing of DNA-PKcs inhibitors for immunosuppression therapy for T cell-mediated autoimmune and immune-related diseases and allogenic graft rejection.…”
Section: Introductionmentioning
confidence: 95%
“…EGR1 was an immune response related transcription factor ( 62 ). EGR1 could induce T cell activation and response ( 63 ). EGR1 was also a signaling intermediate in B-cell antigen receptor stimulated B cell functional response ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…We determined that DNA-PKcs is required for the activity of the transcription factors NFAT, NFκB and EGR1 and the production of the cytokines IL2, IL6, IFNγ and TNFα. [16][17][18] Moreover, we showed that treatment with the DNA-PKcs inhibitor NU7441 extended the survival of transplanted murine allogenic skin grafts by reducing T cell-graft infiltration and inflammatory cytokine production. 17 These studies highlight the immunosuppressive effects of DNA-PKcs inhibitors in vivo.…”
Section: Introductionmentioning
confidence: 92%